2019
DOI: 10.1101/516443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chloroplasts alter their morphology and accumulate at the pathogen interface during infection byPhytophthora infestans

Abstract: Chloroplasts are light harvesting organelles that arose from ancient 20 endosymbiotic cyanobacteria. Upon immune activation, chloroplasts switch off 21 photosynthesis, produce anti-microbial compounds, and develop tubular 22 65 development relies on surface immune signalling, whereas the pathogen subverts this 66 remotely by switching off surface immune pulses. These results implicate chloroplast 67 photo-relocation machinery in plant focal immune responses and demonstrate that 68 chloroplasts play a direct ro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 78 publications
0
14
1
Order By: Relevance
“…These findings, along with related cell biology and biochemical studies, indicate that P. infestans massively reprograms host membrane trafficking during infection (Du et al, 2015;Tomczynska et al, 2018). Membrane trafficking perturbations of haustoriated cells include the rerouting to the haustorial interface of components of the endocytic pathways (Lu et al, 2012;Bozkurt et al, 2015), autophagy machinery (Dagdas et al, 2018;Pandey et al, 2020) and chloroplasts (Toufexi et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…These findings, along with related cell biology and biochemical studies, indicate that P. infestans massively reprograms host membrane trafficking during infection (Du et al, 2015;Tomczynska et al, 2018). Membrane trafficking perturbations of haustoriated cells include the rerouting to the haustorial interface of components of the endocytic pathways (Lu et al, 2012;Bozkurt et al, 2015), autophagy machinery (Dagdas et al, 2018;Pandey et al, 2020) and chloroplasts (Toufexi et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…However, in cells penetrated by multiple haustoria Toufexi et al . (2019) observed chloroplasts clustered around all of them. Given that there is only one nucleus per cell, it is more likely that chloroplasts move to haustoria independently of the nucleus.…”
Section: Host Cell Components Reorganise To Facilitate Defencementioning
confidence: 95%
“…Toufexi et al . (2019) describe clustering of chloroplasts around haustoria. The chloroplasts were observed to extend stromules and wrap haustoria in a chloroplast–stromule network.…”
Section: Host Cell Components Reorganise To Facilitate Defencementioning
confidence: 99%
“…A new study found that chloroplast retrograde signaling can regulate nuclear alternative splicing of a subset of Arabidopsis thaliana transcripts [14,15]. Interestingly, researchers have found that chloroplasts play diverse roles in plant defense, including contributing to the production of defense compounds [16]. Chloroplasts contain their own genome, the chloroplast DNA (cpDNA), which is highly conserved in genomic structure, gene content, and gene order.…”
Section: Introductionmentioning
confidence: 99%